Is placental KISS-1 expression associated with first trimester abortion spontaneous? - Eser Colak; Emel Ebru Ozcimen; Ozgur Hilal Erinanç; Yusuf Aytac Tohma; Mehmet Ufuk Ceran (Korean Society of Obstetrics and Gynecology, 2020)
Objective Several studies have examined biological markers during the first trimester to predict the maintenance of a healthy pregnancy. One such marker is kisspeptin, which is encoded by the KISS-1 gene. We aimed to determine whether first-trimester pregnancy losses were associated with levels of placental KISS-1 expression. Methods This prospective case control study was conducted at a tertiary center. The study group included 27 and 24 patients who underwent dilation and curettage at <10 weeks of gestation, due to first trimester spontaneous pregnancy loss and for elective termination (control), respectively. Placental and decidual tissues from all patients were sectioned and immunohistochemically analyzed for kisspeptin. Results Age, gravida status, parity number, gestational week, and number of previous abortions did not significantly differ between the groups. KISS-1 expression levels were significantly lower in the group with spontaneous abortion compared with the group with elective termination. The median staining intensity of KISS-1 expression in the elective and spontaneous termination groups were 3 (strong) and 2 (moderate), respectively (P=0.004). KISS-1 expression levels were significantly lower among patients with previous abortions in the elective termination group (P=0.002). Conclusion KISS-1 expression levels were found to be significantly reduced in patients with spontaneous pregnancy loss; KISS-1 plays an important role in the implantation and continuation of pregnancy.